State and outlook of agroforestry in ASEAN – Status, trends and outlook 2030 and beyond - Lin, T.; Catacutan, D.C.; Noordwijk, M. van; Finlayson, R.F.; Rogel, C.N.; Orencio P. (Food and Agriculture Organization of the United Nations, 2021)
This report encapsulates the status of and outlook for agroforestry in the ASEAN countries and endeavours to help achieve the SDGs through more sustainable and productive agri-food systems. The status, trends and outlook in this report will support policy makers and practitioners to make appropriate decisions and advance local innovations with agroforestry, especially in the context of the United Nations Decades on Ecosystem Restoration and Family Farming. It will help address the much needed governance, institutional, finance and capacity constraints, especially for promoting smallholder-oriented agroforestry systems in rural areas. Also, the outlook will help enhance the agro-ecological dimensions in land use while yielding more sustainable and productive results combined with ecological and climate-smart outcomes, including those related to Nationally Determined Contributions (NDCs). Eventually, it will contribute to improving the food and nutritional security, livelihoods and wellbeing of marginalized people through sustainable delivery of various ecosystem services.